STRATEGI MENGATASI ANCAMAN KRISIS AIR BERSIH DI KOTA JAYAPURA - , Sepia Ester Waromi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Clean water is an essential element in modern life as both a facilities and infrastructure industries, as well as meet the needs of everyday life. Along with the growth of the construction of an increasing number of people each year continue to rise so that demand for water continues to rise to meet the needs of the community as well as the city of Jayapura with a growth rate of any occupation has increased 4% per year, water demand continues to rise. It is not balanced by the water sources used by the PDAM Jayapura in serving the needs of the community in which the condition of water sources and water damage that bedit mengakibtkan reduce the discharge of water due to several factors, including forest fires, shifting cultivation, mining, quarrying C, clearing land for housing everything is done around the water source. The purpose of this study to determine the strategic issue of Jayapura Regional Water Company in formulating strategy. This study uses the first three theoretical concepts of water resources and water which are all located above water and below the water table, in this sense includes surface water, groundwater, rainwater and seawater. While the understanding of water resources are water and all the potential contained in the water, water resources, including irrigation facilities and infrastructure that have not utilized the second crisis is a situation that was a turning point (turning point) that can make things better or worse added,Water crisis is the dimension of ecological damage for the spread of the earth, the most difficult and most invisible, the third strategy is one of the factors that determine the success of a business or a business, strategic management concept is an attempt to control the organization effectively and efficiently through the implementation of goals and objectives achieved. The research method used in this paper is a descriptive qualitative SWOT analysis techniques, to identify external and internal environment to get the strategic issues that could eventually become an alternative strategy in the management of PDAM Jayapura. The results of this study indicate that the strategy used to solve the problem are: (1) Suppress leakage rate of water in the taps Jayapura, (2) Working closely with governments in conducting oversight of local water resources and strengthen the sanctions, (3) Strategies in Improving Human Resources and PDAM Jayapura Operations Management Optimization, (4) Increased Budget Strtegi is done because the financial aspects of taps Jayapura unhealthy conditions because of the huge debt burden of corporate finance, (5) Improvement of infrastructure, (6) To socialize, (7) Expanding the reach of the service is done because these services will have implications for PDAM Jayapura source of income, (8) minimizes the field of water resources that have been damaged. To keep the water clean and treat the condition in Jayapura city of diminishing it, the strategy should be used Jayapura taps are as follows: 1. Strategies to encourage the rate of leakage of water 2. Strategies to strengthen supervision and sanctions 3. Strategy Improve Human Resourse 4. Strategies to improve the financial condition 5. Strategy of improving infrastructure